1887 N.M. Laws 56, ch. 30, § 4 - (:unkn) unknown (General Publisher, 1887)
Prohibited unlawfully drawing, flourishing, or discharging a rifle, gun, or pistol within the limits of any settlement in the territory. Also prohibited the same in any saloon, store, public hall, dance hall, or hotel. Violators punished by fine not more than one thousand dollars, or by imprisonment not more than three years, or both fine and imprisonment.
--
Keywords: DISCHARGE